Nilai-Nilai Pancasila dalam Komik Cerita Rakyat Asal Kepulauan Riau: Datuk Hitam dan Bajak Laut - Ali, Ahmad Jum'a Khatib Nur (Ideas Publishing, 2024)
Folklore is one of the mediums used to teach Pancasila values. This research objective is to reveal the Pancasila values presented in Datuk Hitam and the Pirates folklore. This research is limited on the visual and verbal aspects of the comic as research object. The method used in this research is qualitative with narrative structure and signification theories. The findings of research results show that the research object has a complete narrative structure and contains values of the 3rd and 4th principles. The narratives and significations presented are: placing the interests of the nation and state above the personal interests; willingness to sacrifice for the nation and state; goodwill and responsibility to accepting and implementing the results of deliberations. These two principles are conveyed through the characterization of Datuk Hitam, as well as through the visual and verbal texts of the digital comic. This research results findings can contribute to the folklore study, especially the use of comic as medium for conveying Pancasila values.